MANAGING FORMER LANDFILL SITES A CASE STUDY OF ECORESTORATION FROM KOCHI, KERALA - Chandran, Smitha (Green Chemistry & Technology Letters, 2016)
This paper describes the dramatic success in the eco-restoration of a heavy-metal contaminated open garbage dump at the Amrita Institute of Medical Sciences (AIMS), a 1450-bed super-specialty hospital located in Kochi, Kerala, India. Today, the hospital caters to over 10 lakh patients annually. Inspired by our Chancellor’s vision of zero-waste, the hospital undertook its journey with a view to also reducing massive greenhouse gas emissions that result from improper handling of waste. Today, the hospital manages its municipal solid waste on an industrial scale, composting some eight metric tonnes of organic waste daily. This case study outlines the path followed to achieve zero-waste. Alongside, the rehabilitation of a former dump site is described in detail at this very site are carried out all composting operations of AIMS. Within three years of the restoration activities, heavy metal concentrations in the contaminated soil reduced drastically. There was relatively low uptake of the heavy metals by the plants; however, they might have been crucially responsible for providing a favorable environment for soil restoring microorganisms in their rhizosphere. Observable habitat-restoration continues at the site, including the return of birds and insects and other wildlife, making this an ideal site for further research and demonstration for community awareness and education.